Germany : Financial Sector Assessment Program-Detailed Assessment of Observance on Eurex Clearing AG Observance of the CPSS-IOSCO Recommendations for Central Counterparties. (IMF Staff Country Reports; Country Report, 2011)
Eurex has a sound, transparent, and enforceable legal basis to address the legal risks related to its activities. Eurex is regulated and supervised as a bank. Its clearing activities are governed by a consistent and solid set of laws, regulations, rules, and instructions. Eurex has a comprehensive risk management framework composed of objectives, measures, and tools defined at the level of Eurex and that of the Deutsche Borse Group (DGB). Eurex regularly reviews its pricing, service, and capacity level, and is regulated and supervised by several authorities.